2021
DOI: 10.1186/s12893-021-01107-4
|View full text |Cite
|
Sign up to set email alerts
|

Further understanding on osteopetrotic femoral fractures: a case report and literature review

Abstract: Background Osteopetrosis is a genetic disease characterized by defects in osteoclast formation and function. There were a few cases of subtrochanteric femur fractures treated with dynamic hip screw (DHS) in patients with osteopetrosis, but unfortunately the healing outcome was rather poor. Case presentation We present our experience for treating a patient with intermediate autosomal recessive osteopetrosis (IRO) suffering from subtrochanteric femur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, as Ding et al highlight in their report, after 2005, with the accumulation of clinical and operative experience in the treatment of osteopetrosis-associated fractures, reports of complications after surgical treatment decreased significantly. They report that the complication rate decreased from 54.5% to 21% after 2005 12 .…”
Section: Discussionmentioning
confidence: 99%
“…However, as Ding et al highlight in their report, after 2005, with the accumulation of clinical and operative experience in the treatment of osteopetrosis-associated fractures, reports of complications after surgical treatment decreased significantly. They report that the complication rate decreased from 54.5% to 21% after 2005 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Since Ding et al reported that occlusion of the medullary cavity and femoral malformation limited the application of intramedullary fixation, DHS fixation was used. At the same time, two sets of surgical instruments were prepared for use alternately, along with sterile ice-cold saline irrigation for cooling down, to solve the problem of overheating the drill, which aided the successful completion of the operation [ 9 ] ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, two sets of surgical instruments were prepared for use alternately, along with sterile ice-cold saline irrigation for cooling down, to solve the problem of overheating the drill, which aided the successful completion of the operation [ 9 ] ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…T HA in patients with osteopetrosis has been reported as an effective procedure in treatment of osteoarthritis; however, it is a challenging procedure with prolonged operative time [3][4][5][6][7][8][9][10][11] . THA after prior surgical treatment of hip fracture is a technically demanding procedure 12 .…”
Section: Discussionmentioning
confidence: 99%